Public Beliefs about Lightning in Malaysia - Syakura A.R.; Gomes C.; Trengove E.; Ab Kadir M.Z.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Accident prevention; Lightning; Lightning protection; beliefs; Human risks; injuries; Malaysia; religion; Surveys